Evaluation of the Bureau of Justice Assistance Mental Health Court Initiative at Seven Sites in the United States, 2003-2004 - Steadman, Henry J. ([Verlag nicht ermittelbar], 2005)
This study evaluated seven mental health courts that were partially funded by the Bureau of Justice Assistance. Data were collected on 285 formal referrals to the seven courts between November 1, 2003, and January 31, 2004. For every referral, court staff completed a one-page questionnaire that covered (1) identification of the referring agent, (2) characteristics of the referred person, including age, gender, race, criminal charges, and type of mental disorder, and (3) the disposition decision.